Probiotic viability, pH and lactic acid concentration of opened commercial probiotic dairy drinks stored at different temperatures and durations - Liew, Yun Khoon (2023)
Total probiotic viability of different commercial fermented dairy drinks stored under different temperature–time conditions after opening The initial amount of total viable bacteria in the commercial probiotic dairy drinks branded Y, F, N and V was 11 log CFU/mL, 7.08 log CFU/mL, 7.36 log CFU/mL and 10.05 log CFU/mL, respectively. Remarkably, the low density of probiotics was detected in products F and N.